2022
DOI: 10.3390/mi14010052
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Wideband Transition from LTCC Laminated Waveguide to Air-Filled Rectangular Waveguide for W-band Applications

Abstract: In this paper, a novel wideband transition from a laminated waveguide (LWG) to an air-filled rectangular waveguide (RWG) is proposed for millimeter-wave integration solutions based on multilayer low-temperature co-fired ceramic (LTCC) technology. The integrated transition cavity is divided into several resonators by introducing five grounded via holes. Due to the magnetic wall existing in the symmetry plane, the equivalent circuit of the proposed transition can be simplified as a three-pole filter model to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…To facilitate the measurement in W-band, a compact vertical transition from SIW to rectangular waveguide (RWG) is designed and integrated in the LTCC module. The wideband working mechanism of this transition are presented in our another work [22]. To verify the feasibility of the proposed antenna scheme, a prototype of the designed 2 � 4 antenna array is fabricated using multilayer LTCC technology.…”
Section: Overall Design Of 2 £ 4 Antenna Arraymentioning
confidence: 99%
See 2 more Smart Citations
“…To facilitate the measurement in W-band, a compact vertical transition from SIW to rectangular waveguide (RWG) is designed and integrated in the LTCC module. The wideband working mechanism of this transition are presented in our another work [22]. To verify the feasibility of the proposed antenna scheme, a prototype of the designed 2 � 4 antenna array is fabricated using multilayer LTCC technology.…”
Section: Overall Design Of 2 £ 4 Antenna Arraymentioning
confidence: 99%
“…The simulated radiation efficiency is about 70% within the working band, while the measured radiation efficiency is not obtained due to the test system limitation in the laboratory. To calibrate the measured radiation gain of the proposed antenna array, two back-to-back transitions are designed and fabricated to estimate the feeding SIW [22]. It is demonstrated that the insertion loss of 12 mm-SIW is about 0.96 dB.…”
Section: Overall Design Of 2 £ 4 Antenna Arraymentioning
confidence: 99%
See 1 more Smart Citation